2016
DOI: 10.1002/2016ja022659
|View full text |Cite
|
Sign up to set email alerts
|

LSWS linked with the low‐latitude Es and its implications for the growth of the R‐T instability

Abstract: A comprehensive investigation of spread F irregularities over the Indian sector has been carried out using VHF radar and ionosonde observations. Two different categories of spread F observations, one where the onset of the range spread F (RSF) was concurrent with the peak h′F (category 1) and another where the RSF onset happened ~90 min after the peak h′F time (category 2), are presented. RSF in category 2 was preceded by the presence of oblique echoes in ionograms, indicating the irregularity genesis westward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…One can see that the peak h ′ F in the first category is somewhat higher than that in the second category, while the time of the peak h ′ F is the same. Recently, Joshi () also reported similar difference in the h ′ F in these two categories of radar plume events based on the observations using the Indian MST radar at Gadanki. Unlike the Gadanki radar with fixed radar beam, EAR has the scanning capability to observe the spatial‐temporal behavior of the EPB.…”
Section: Resultsmentioning
confidence: 62%
“…One can see that the peak h ′ F in the first category is somewhat higher than that in the second category, while the time of the peak h ′ F is the same. Recently, Joshi () also reported similar difference in the h ′ F in these two categories of radar plume events based on the observations using the Indian MST radar at Gadanki. Unlike the Gadanki radar with fixed radar beam, EAR has the scanning capability to observe the spatial‐temporal behavior of the EPB.…”
Section: Resultsmentioning
confidence: 62%
“…It is known that several upwelling in electron density can often exist at the bottomside of F region in the form of wave referred to as large‐scale wave structures (LSWS) [ Tsunoda and White , ]. Studies in recent past have shown that the LSWS evolves as a standing wave with insignificant zonal propagation [ Tsunoda and Ecklund , ; Patra et al , ; Joshi , ]. Also, It is demonstrated that these LSWS remain present in the ionosphere even after the generation of the plasma bubble, and its signature can be seen in radar maps as the bottomside modulation of F region [ Kelley et al , ; Patra et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Day‐to‐day variability of equatorial plasma bubble (EPB) continues to be extensively investigated even decades after its discovery, not only due to scientific interest but also due to its detrimental effects on the navigation/communication systems. While it is possible to forecast the solar cycle and seasonal behavior of EPBs over different longitude sectors (Joshi et al, ; Nishioka et al, ; Smith & Heelis, ), understanding their intraseasonal variability remains one of the most important aspects of ionospheric research (Hysell et al, ; Joshi, ; Joshi, Patra, Pant, & Rao, ; Joshi, Patra, & Rao, ; Joshi et al, ; Tsunoda, ). Not only the day‐to‐day variability of EPBs is a concern, but the phenomenon has been found to be impacted by planetary‐scale forcing (Abdu et al, ; Abdu & Brum, ; Bertoni et al, ; de Abreu et al, ; Fagundes et al, ; Liu et al, ; Takahashi et al, , ).…”
Section: Introductionmentioning
confidence: 99%